Cover Feature: Investigating a Boronate‐Affinity‐Guided Acylation Reaction for Labelling Native Antibodies (Chem. Eur. J. 17/2022). Issue 17 (26th February 2022) - Adak, Avijit K.; Huang, Kuan‐Ting; Liao, Chien‐Yu; Lee, Yuan‐Jung; Kuo, Wen‐Hua; Huo, Yi‐Ren; Li, Pei‐Jhen; Chen, Yi‐Ju; Chen, Bo‐Shiun; Chen, Yu‐Ju; Chu Hwang, Kuo; Wayne Chang, Wun‐Shang; et al.
Abstract : A boronic acid based biorthogonal probe in combination with an acyl donor has been introduced that enables site‐specific incorporation of azide group at the Ser and Tyr residues of nonengineered full‐length antibody. Further derivatization of this functional site was accomplished through click reaction, yielding well‐defined immunoconjugates. The generality of this boronate‐affinity method has been demonstrated on a number of monoclonal antibodies, all with different binding specificities. More information can be found in the Research Article by W.‐S. Wayne Chang, C.‐C. Lin et al. (DOI: 10.1002/chem.202104178 ).